The rights and roles of parents on school governing bodies in South Africa - Van Wyk, Noleen (International Journal about Parents in Education, 2023)
The South African Schools Act of 1996 mandates the establishment of school governing bodies (SGBs) comprising parents, educators and non-educator members of staff. Since parents form the majority on SGBs they have been placed in a powerful position and are able to influence the school budget, language policy, discipline and the appointment and promotion of teaching and administrative staff. In addition, the new structure of school governance provides the opportunity to establish a new relationship between the state and parents, set a new direction for education, and provide a learning space where the critical skills of civic capacity might be extended. This paper examines the extent to which this has been achieved. Data was obtained by means of a questionnaire completed by parents and teachers, followed by in-depth interviews with selected principals and school governing body members. Findings suggest that problems still exist around issues of marginalisation of black parents in racially mixed schools, levels of education of parent governors, poverty and lack of resources in rural communities and a lack of understanding between governance and management of schools. Ways in which the rights and roles of parents in school governance can be improved are included in the paper.